Assessment of Pregnant Women Knowledge and Practices Concerning Iron Deficiency Anemia at Al-Amara City/Iraq (Medico Legal Update, 2020)
Objectives: To assess knowledge and practices related to the prevention of iron deficiency anemia amongpregnant women and to find an association between their knowledge; practices and socio-demographicvariables. Methodology: This is an institutional descriptive study conducted on the random selection ofsix primary healthcare centers in Al-Amara city. A purposive sampling technique was used to select (280)pregnant mothers attending antenatal care service.Results: Almost half of the sample belongs to the primary education level (50.3%) and most of themhousewife (56.8%), with low monthly income (71.8%). Over three quarters of the sample had moderateknowledge (76.1%) and their unfavorable practices (75.5%) with regard to iron anemia. The results indicateda high relationship between the knowledge and practice of women with the variables under study (p= 0.000).Conclusion: The study concluded that the majority of participants have insufficient knowledge with moderatepractices towards preventing this type of anemia. Health education about foods with a high concentration ofiron is an essential step towards reducing iron deficiency anemia in pregnant women.